Stereolithography (STL) model in dental autotransplant: A case report - Wan Zullkefli, Wan Nur Zahidah; Chi Adam, Khairul Bariah; Jamali, Nabilah Rashida (IIUM Journal of Orofacial and Health Sciences, 2024)
The goal of this case report was to describe the use of the stereolithography (STL) model in dental autotransplantation. This report described autotransplantation of the lower wisdom tooth (48) to replace a missing lower first molar (46) due to caries. This approach used an STL model of 48 fabricated in the laboratory from cone-beam computed tomography (CBCT) images to assist in recipient site preparation before autotransplant. In conclusion, the use of the STL model could potentially increase the success rate of autotransplantation as it can help to preserve the periodontal ligament (PDL) cells on the root surface of the donor tooth, shorten the extraoral time of the donor tooth, and provide optimum contact between the recipient bone and the root surface of the transplanted tooth.